Clinical and molecular determinants of extrahepatic disease progression in patients with metastatic colorectal cancer with liver-limited metastases deemed initially unresectable. Issue 2 (9th May 2019) - Ongaro, Elena; Cremolini, Chiara; Rossini, Daniele; Corti, Francesca; Pagani, Filippo; Morelli, Luca; Urbani, Lucio; Masi, Gianluca; Sposito, Carlo; Filippi, Beatrice; Borelli, Beatrice; Zucchelli, Gemma; et al.
Abstract : Background: No tools to predict the probability of extrahepatic disease progression (ePD) of initially unresectable, liver-limited metastatic colorectal cancer (mCRC) are currently available. To estimate the likelihood to develop ePD and to identify clinical and molecular factors that could predict extrahepatic progression-free survival (ePFS), we conducted an observational, retrospective, multicentre cohort study. Methods: We retrospectively identified a cohort of 225 patients with initially unresectable liver-limited disease (LLD), treated from January 2004 to December 2017 with first-line doublets or triplet plus a biological agent at two Italian institutions. Results: 173 (77%) patients experienced ePD which occurred within 1, 2 or 3 years from the diagnosis of mCRC in 15%, 49% and 66% of patients, respectively. Globally, 164 (73%) patients underwent a liver resection at some point of their disease history, and 54 (33%) of them underwent a subsequent locoregional treatment. Age > 70 years, locoregional nodal involvement at diagnosis of colorectal cancer and ≥4 liver metastases were significantly associated with higher risk of ePD while liver resections were associated with reduced risk of ePD. In the multivariable model, number of liver metastases (subdistribution HR, SHR 1.63, 95% CI 1.12 to 2.36; p = 0.01) and liver resections (SHR 0.43, 95% CI 0.29 to 0.63; p = 0.001) were still associated with ePD. Number of liver metastases < 4, no nodal involvement at diagnosis and liver resections were also associated with prolonged ePFS. Conclusions: The identified clinical factors could help physicians in personalising the intensity and aggressiveness of liver-directed treatments in patients with mCRC with initially unresectable LLD.